Challenges to Use Open Government Data through the Citizens’ Lens: A Systematic Review - Nosheen Fatima Warraich; Tayyaba Rasool; Muhammad Sajid (Journal of Political Studies, 2019)
This study aims to explore the challenges to use open government data (OGD) among citizens . To meet the objective of the study, it used a systematic review by reviewing the published literature and followed Preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) guidelines. The study identified the challenges affecting the citizens’ satisfaction to use OGD including technological skills, retrieval of data, usability, quality of data, timelines, and accuracy. The OGD also lacks in standardization, the relationship between citizens and government, and awareness to use this data. This study will fill the knowledge gap by identifying the barriers in using OGD. It may help to increase awareness towards the OGD portals among policymakers and practitioners and they should consider the underlying barriers in reusing the data.